Maternal Knowledge about Breastfeeding Techniques and Burping Techniques with Regurgitation Events in Infants 0-6 Months - Purbasary, Eleni Kenanga; Mukidin, Ali Musthofa Bin; Yuneri, Yuneri (Sarana Ilmu Indonesia (salnesia), 2025)
Regurgitation is the release of part of the milk that has been swallowed through the mouth without force. The factors that play a role in the occurrence of regurgitation is the mother's level of knowledge regarding proper breastfeeding and burping techniques. This study aimed to analyze the relationship between maternal knowledge about breastfeeding techniques and burping techniques with the frequency of regurgitation. The study design was cross-sectional with a population of breastfeeding mothers aged 0–6 months in the Karangampel Health Center work area. Total sampling with 96 subjects. Data were collected through questionnaires. The results of the study showed that 25 mothers (67,6%) had sufficient knowledge about breastfeeding techniques, with occasional regurgitation p-value 0,000 (p-value<0,05) indicating a significant relationship. A total of 37 mothers (77,1%) had sufficient knowledge about burping techniques, also with occasional regurgitation p-value 0,000 (?0,05). Maternal knowledge plays an important role in the implementation of correct breastfeeding and burping techniques. Therefore, every mother needs to understand and practice these techniques well. Given the importance of the influence of knowledge on preventing regurgitation, it is recommended that health workers routinely provide education on correct breastfeeding and burping techniques to reduce the risk of regurgitation in infants.